Taking sides : clashing views on controversial issues in secondary education - Evans, Dennis L. (Guilford, Conn. : McGraw Hill/Dushkin, 2002)
Twenty debates in secondary education; ethnocentric education, school uniforms, block scheduling, and more. Requiring students to analyze opposing viewpoints and reach considered judgments, Taking Sides actively develops students' critical thinking skills.
Pt. 1 Purposes: Should school attendance be voluntary? -- Is citizenship education working in the public schools? -- Should all secondary school students experience the same curriculum? -- Is ethnocentric education a good idea? -- Should secondary schools emphasize education for the workplace? -- Pt. 2 Policies: Should religious content and concepts be more evident in our schools? -- Do school uniforms cause improvements? -- Are zero tolerance policies necessary and effective? -- Is achievement level tracking of students a defensible educational practice? -- Is high-stakes standardized testing defensible? -- Should teacher pay be tied to measures of student learning? -- Is the school principal indispensable? -- Pt. 3 Practices: Is block scheduling better than traditional scheduling? -- Is homework beneficial to students? -- Does the practice of grading students serve useful purposes? -- Can technology transform education? -- Should service learning be a high school graduation requirement? -- Is the emphasis on globalization in the study of world history appropriate? -- Should classical works be the emphasis of the high school literature curriculum? -- Should we be cheering for high school sports programs?
Includes bibliographical references and index.
Donation from the Asia Foundation
Keywords: Education, Secondary -- United States; Education, Secondary -- Social aspects; High schools -- United States